2020
DOI: 10.1017/s0022029920000357
|View full text |Cite
|
Sign up to set email alerts
|

Timing of entry of Streptococcus uberis into the mammary gland of the dairy cow

Abstract: Streptococcus uberis do not colonise the teat canal and appear to invade the mammary gland of the dairy cow by direct entry though the canal. When they enter the mammary gland, and the early resulting processes, are unclear. Experimental infusions of the lactating mammary gland have been made to determine outcomes of infection, mastitis and disease. Infusion of 500 cfu bacteria was made immediately after milking (8 and 16 h intermilking interval) and 1, 4 or 12 h prior to milking. A mastitis resulted from all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The bacteria may then possibly colonise the teat-end(s) of the animals milked subsequently, which can potentially lead to an increase in intramammary infections. In a recent challenge study, Hillerton (2020) reported that streptococci could cause clinical mastitis more frequently if infused immediately after milking than at other times in relation to milking. This may possibly be allied to a potential transmission of the bacteria from the teatcups to ewes occurring during milking.…”
Section: Discussionmentioning
confidence: 99%
“…The bacteria may then possibly colonise the teat-end(s) of the animals milked subsequently, which can potentially lead to an increase in intramammary infections. In a recent challenge study, Hillerton (2020) reported that streptococci could cause clinical mastitis more frequently if infused immediately after milking than at other times in relation to milking. This may possibly be allied to a potential transmission of the bacteria from the teatcups to ewes occurring during milking.…”
Section: Discussionmentioning
confidence: 99%